Digitalisasi Media Pembelajaran dalam Meningkatakan Hasil Belajar dan Aktivitas Peserta Didik - Khusnah, Wakhibah Dwi (Al-Muttaqin : Jurnal Studi, Sosial, dan Ekonomi, 2024)
Media digitalization has changed the traditional learning paradigm by providing new opportunities for students to acquire skills and knowledge. This research aims to determine the impact of the digitalization of learning media on learning outcomes and student activities. The method used is descriptive qualitative. The research results show that the digitalization of learning media has a positive impact on learning outcomes and student activities. Student learning outcomes increased from 60% to 90%. The results of student activities are also very good. The digitalization of learning media helps students learn skills such as collaboration, communication, independence, and discipline. Apart from that, the use of digital media enables students to be able to solve problems and manage time. Keywords: Digitalization, learning media, learning results, student activities.